Chronic myeloid leukemia in children and adolescentes: An analys of cases (Research, Society and Development, 2024)
Objective: to analyze the characteristics and evolution of patients diagnosed with chronic myeloid leukemia at a reference center in pediatric oncology in the western region of paraná. Method: analytical, descriptive, and retrospective study composed of medical records of pediatric oncology patients from the Cancer Hospital of Cascavel-UOPECCAN, between january 2002 and january 2022. Results: seven medical records were analyzed. Among these, 5 (71%) were male and 2 (29%) were female. The median age at diagnosis was 12 years and 1 month. The average time from symptom onset to diagnosis was 2 months and 5 days. Two (29%) patients were diagnosed in less than 30 days, 3 (43%) between 30 and 60 days, and 2 (29%) in more than 60 days. The most common clinical manifestations were weight loss (57%), splenomegaly (43%), fever (29%), and bruising (29%). Regarding clinical treatment, 2 (29%) patients showed a good therapeutic response to imatinib mesylate and remain on the medication, 3 (43%) required a switch to nilotinib, 1 (14%) patient who did not respond to both previous drugs required hematopoietic stem cell transplantation, and 1 (14%) experienced a blast crisis of acute leukemia, necessitating a distinct therapeutic approach. Out of the 7 analyzed medical records, 6 (86%) patients remain alive. Conclusion: based on this study, it is concluded that early diagnosis, recognition of the disease's clinical phase, and appropriate treatment are important factors influencing the prognosis and survival of these patients. Therefore, studies on this malignant neoplasm are of utmost importance.